2023
DOI: 10.3390/electronics12143036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Full-Reference Quality Assessment Metrics in End-to-End Deep Video Coding

Abstract: Visual quality assessment is often used as a key performance indicator (KPI) to evaluate the performance of electronic devices. There exists a significant association between visual quality assessment and electronic devices. In this paper, we bring attention to alternative choices of perceptual loss function for end-to-end deep video coding (E2E-DVC), which can be used to reduce the amount of data generated by electronic sensors and other sources. Thus, we analyze the effects of different full-reference qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The findings highlighted the importance of screen size in perceived video quality and the limitations of existing objective quality models in capturing the effect of screen size changes. The issue of video compression and its relation to user perception is also studied in [30].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings highlighted the importance of screen size in perceived video quality and the limitations of existing objective quality models in capturing the effect of screen size changes. The issue of video compression and its relation to user perception is also studied in [30].…”
Section: Related Workmentioning
confidence: 99%
“…For the medium compression cluster associated with the VIDEO CRF input variable, we observed that the standard Gauss2 function did not fully align with the underlying data As in Figure 2, the x-axes values in Figure 3 correspond with the properties of the video sequences discussed in Section 3.1. Specifically, there were six different video frame rate values (24,30,60,82,98, and 120 fps), with CRF values ranging from 0 to 63, depending on the fps and the resulting bitrate. To compute the SI and TI values, we utilized the MSU Quality Measurement Tool (version 14.1) [43], calculating them for each of the 480 test sequences and then multiplying them by 1000 to enable clustering.…”
Section: Fuzzification Of the Scalarsmentioning
confidence: 99%